Utilization of Protruded Strip Resonators to Design a Compact UWB Antenna with WiMAX and WLAN Notch Bands - Mazloum, J.; Ojaroudi, N. (The Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a new design of ultrawideband (UWB) microstrip monopole antenna is presented. The main novelty of the proposed structure is the using of protruded strips as resonators to design an UWB antenna with dual band-stop property. In the proposed design, by cutting the rectangular slot with a pair of rotated Y-shaped strips in the ground plane, additional resonance is excited and much wider impedance bandwidth can be achieved. To make a single band-notched function, the square radiating patch is converted to the square-ring structure with a pair of protruded fork-shaped strips. Finally, by cutting a rectangular slot with a protruded M-shaped strip at the feed line, a desired dual band-notched function is achieved. The measured results reveal that the presented dual band-notched antenna offers a very wide bandwidth from 2.8 to 11.6 GHz, with two notched bands, around of 3.3-3.7 GHz and 5-6 GHz covering all WiMAX and WLAN bands.